How do the STAD cooperative learning model, conventional methods, and student confidence affect football learning outcomes? - Atradinal, Atradinal; Ockta, Yovhandra (Jurnal Konseling dan Pendidikan, 2024)
This study evaluates the impact of the STAD-type cooperative learning model versus the conventional model on football learning outcomes for Grade VIII students at Junior High School 2 Sijunjung, focusing on students' confidence levels. It addresses the low football learning outcomes associated with conventional teaching methods, which often lead to reduced engagement. The research aims to explore the interaction between learning models and student confidence, compare the effectiveness of both models, and examine differences in outcomes for high and low confidence students. Using a quasi-experimental method, the study involved 82 male students, categorized by confidence level and instructed through either the STAD or conventional model. Data were collected via confidence questionnaires and football skill tests, analyzed using two-way ANOVA and Tukey’s test. Findings indicate that the STAD model is more effective in improving football learning outcomes, particularly for students with low confidence. Conversely, high confidence students performed better with the conventional approach. This highlights the significant role of confidence in learning outcomes and suggests that collaborative settings benefit less confident learners. The study concludes that tailoring teaching methods to students' confidence levels can enhance engagement and performance. Future recommendations include strategies to boost student confidence, further improving physical education outcomes.